Application of Aluminum Oxide Nanoparticles in Aspergillus terreus Cultivations: Evaluating the Effects on Lovastatin Production and Fungal Morphology. - Boruta, Tomasz; Bizukojc, Marcin (BioMed Research International, 2019)
Aluminum oxide nanoparticles were supplemented to Aspergillus terreus ATCC 20542 precultures and the outcomes of the process were evaluated relative to the results of microparticle-enhanced and standard cultivations. The selected morphological parameters of fungal pellets (projected area, elongation, convexity, and shape factor) were monitored throughout the experiment, together with biomass, lactose, and lovastatin concentration. The qualitative and quantitative chemical analysis was performed with the use of liquid chromatography coupled with high resolution mass spectrometry. The results of the study indicated that the application of nanoparticles was indeed associated with morphological consequences, most notably the decreased pellet size. However, it turned out that the term "nanoparticle-enhanced cultivation" could not be used in the context of lovastatin production, as no marked increase of product titer was observed in nanoparticle-influenced variants relative to standard and microparticle-enhanced cultivation. In addition, the concentration of biomass in the nanoparticle-influenced runs was relatively low. Comparative analysis of total ion chromatograms revealed the presence of a molecule of unknown structure that could be detected solely in broths from standard and microparticle-containing cultures. This study represents the first evaluation of nanoparticles as the tools of morphological engineering aimed at enhanced lovastatin biosynthesis in A. terreus cultures.